Penerapan Model Project Based Learning dengan Media Video untuk Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran Bahasa Indonesia Kelas 3 SDN 48 Cakranegara - Herawati, Aina; Amrullah, Amrullah; Nurhayati, Hj (TSAQOFAH, 2023)
This research aims to determine the improvement in participant learning outcomes class 3A students at SDN 48 Cakranegara using the Project Based Learning model with educational video media. This research includes collaborative PTK research with a descriptive qualitative approach. This research was carried out in stages in two cycles. The subjects of this research were all class 3A students at SDN 48 Cakranegara for the 2022/2023 academic year. Classroom action research (PTK) is carried out in 2 cycles consisting of planning, action implementation, observation, evaluation and reflection stages. Each cycle consists of one meeting. The results of this research show an increase from cycle to cycle. Then there was an increase until in cycle II, where there was a significant increase in learning outcomes. This shows that the application of a project-based learning model with video media can improve Indonesian language learning outcomes for class 3A students at SDN 48 Cakranegara.